Denitrification within the sediments and epiphyton of tropical macrophyte stands. Issue 3 (3rd July 2021) - Adame, Maria Fernanda; Waltham, Nathan J.; Iram, Naima; Farahani, Bahareh Shahrabi; Salinas, Cristian; Burford, Michele; Ronan, Mike
ABSTRACT: Excess nitrogen (N) is one of the most widespread and serious pollutants in the environment, but wetlands can reduce N loads, ameliorating its damaging effects downstream. Tropical wetlands are highly productive and experience high temperatures year-round, resulting in potentially high denitrification rates. However, few measurements of denitrification have been reported for tropical wetlands. In this study, we measured denitrification within stands of macrophytes at the edge of a tropical lake (900 m length, 4 m deep) in Australia. We compared denitrification rates among sediments under emergent grass (giant bulrush, Actinoscirpus grossus ), sediments under floating waterlilies ( Nymphae spp.), and sediments from the deeper sections of the lagoon with no macrophytes. We also measured the denitrification and primary productivity of the epiphyton on macrophytes and compared the rates with those from the sediment. Denitrification in the sediment was higher (Dt = 3.3–52 mg m −2 h −1 ) than denitrification of the epiphyton (Dt = 1.9–3.6 mg m −2 h −1 ) and was mostly coupled with nitrification (Dn ). Denitrification was highest in sediments rich in organic carbon (32.3%) and N (1.4%), and during times of the year when nitrates (NOx − -N = NO2 − -N + NO3 − -N) concentrations were relatively high (>0.10 mg L −1 ). Denitrification was lowest in sediments with no macrophytes, which comprised most of the lake area. Denitrification rates of sediments under these macrophyte stands were among the highest values measured for natural wetlands and highlight the potential role of this process in ameliorating N pollution in tropical catchments.